Women and Common Property Resources: A Case Study of Rural Awadh Tarai - Singh, Ravi S.; Singh, Ankita (National Geographical Journal of India, 2022)
Rural women and men share different tasks and responsibilities which results in different needs, priorities and concerns. Although these responsibilities vary across regions and cultures, but rural women often follow similar gender division of labour. In most of the cases, rural women have the responsibility for the collection of fuel-wood, food and fodder for animals for which they are heavily dependent on common property resources. Men seldom have responsibility for collecting and using natural resources for household use. Based on primary data generated through fieldwork, the present paper delves into role played by CPRs in the lives of rural tribal women of Awadh Tarai.